Linkages of Enzymatic Activity and Stoichiometry with Soil Physical-Chemical Properties under Long-Term Manure Application to Saline-Sodic Soil on the Songnen Plain - Cheyu Zhai; Xiaotong Feng; Changjie Liu; Yang Li; Jiaming Fan; Juan Zhang; Qingfeng Meng (Agronomy, 2023)
Excess Na+ and high pH result in poor structures in Saline-Sodic soils, which reduces extracellular enzyme activity (EEA) and causes nutrient limitations. The application of manure improved the Physical-Chemical properties of soil and balanced the soil nutrient supply, which was reflected in the soil EEAs and stoichiometry. Five experimental treatments were designed according to the manure application duration as follows: manure application for 11 years (11a), 16 years (16a), 22 years (22a), and 27 years (27a) and a control treatment with no manure application (CK). The results of the redundancy analysis (RDA) showed that physical properties (mean weight diameter (MWD)) and EEA (β–glucosidase (BG)) significantly increased and bulk density (ρb) significantly decreased when the nutrient content increased. Additionally, soil pH, electrical conductivity (EC), exchangeable sodium percentage (ESP) and sodium adsorption ratio (SAR) significantly decreased after manure application. Based on stepwise multiple linear regression models (SMLR), total nitrogen (TN) was the dominant variable that significantly increased EEA, and the Mantel test showed that soil C:N significantly influenced enzyme stoichiometry. Furthermore, RDA showed that pH, soil C:N and TN were the main factors influencing EEAs and enzyme stoichiometry. Soil EEAs significantly increased with TN and decreased with pH and soil C:N, which affected enzyme stoichiometry. The enzyme stoichiometry increased from 1:2.1:1.2 and 1:2.7:1.5 to 1:1.7:1.2, and the vector angle (vector A) increased, which showed that the N limitation was relieved after the application of manure. The vector length (vector L) showed no significant difference in the C limitation at depths of 0–20 cm and significantly increased at depths of 20–40 cm. In conclusion, soil EEAs and stoichiometry improved with changes in TN and soil C:N, and pH decreased with changes in the soil structure after the application of manure, which accelerated the soil nutrient cycle and balanced the soil nutrient supply.